Benefits of Artesunate versus Quinine in the Treatment of Children with Severe Malaria at the National University Teaching Hospital of Cotonou - SAGBO, GODONOU GRATIEN; ZOHOUN GUIDIBI, LUTECIA MYRIAME; BOGNON, GILLES (My University, 2017)
Introduction: Severe malaria is one of the leading causes of death in Sub-Saharan African countries, and artesunate is recommended as a first-line treatment by the Word Heath Organization (WHO.). Objective: Identify the advantages of artesunate compared with quinine in the treatment of severe malaria in children. Methods and patients: This study was a cross-sectional, descriptive and analytical study focused on children hospitalized for severe malaria in the CNHU who were treated with quinine or artesunate. Findings: The hospital-based frequency rate of severe malaria in pediatric patients was estimated to be 28.3% (n = 848). One hundred five children were treated with artesunate, and 743 were treated with quinine. The mean age of the children was 47 months old. The primary signs of severity were anemia (n = 776), neurological manifestations (n = 309) and hemolysis (n = 137). The average duration of treatment was 1.95 days for artesunate versus 2.45 days for quinine, and the difference was statistically significant (p = 0.001). The average length of stay (ALOS) in the hospital was 5 days for the artesunate group versus 5.75 days for the quinine group, and the difference was statistically significant (p < 0.001). Six of the children who received artesunate died, whereas 24 children who treated with quinine died. The total average cost of healthcare was 50,600 FCFA (77 euros) per child treated with artesunate versus 57,100 FCFA (87 euros) per child treated with quinine. Conclusion: The treatment of severe malaria with artesunate is superior to quinine-based treatment.
Keywords: Severe Malaria; Quinine; Artesunate